2016
DOI: 10.1038/srep37843
|View full text |Cite
|
Sign up to set email alerts
|

Characterizations of H4 avian influenza viruses isolated from ducks in live poultry markets and farm in Shanghai

Abstract: H4 avian influenza virus is one of the most prevalent influenza virus subtypes in birds. The evolution and pathogenicity of H4 AIV in domestic birds of China remain largely unclear. In the present study, a total of eight H4 AIV strains isolated in duck farm and live poultry markets (LPM) were characterized. Phylogenetic analysis indicated that these strains are divided into two groups in the Eurasian lineage. Eight genes of MH-2/H4N6 isolated from a duck farm were closely related to three H4N6 viruses from LPM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 36 publications
0
33
0
Order By: Relevance
“…Since the first H4 strain was isolated from a duck in the former Czechoslovakia in 1956, the H4 LPAIV has been discovered to be widely circulating in wild and domestic avian species in Asian, European, and North American countries (Bui et al, 2012;Donis et al, 1989;Kang et al, 2013;Liang et al, 2015;Teng et al, 2012;Wu et al, 2015;Yuan et al, 2015). In recent years, multiple genotypes of H4 viruses have been shown to be co-circulating in the live poultry markets of Central, Eastern, and Southern China, and complex reassortment events between H4 subtype viruses and other subtype viruses (e.g., H3 subtype virus) have actively occurred in domestic ducks (Deng et al, 2013;Liang et al, 2015;Shi et al, 2016;Wu et al, 2015;Yuan et al, 2015). H4 subtype viruses can replicate in mice without prior adaptation and transmit between guinea pigs via direct contact (Kang et al, 2013;Liang et al, 2015).…”
Section: Accession Numbersmentioning
confidence: 99%
“…Since the first H4 strain was isolated from a duck in the former Czechoslovakia in 1956, the H4 LPAIV has been discovered to be widely circulating in wild and domestic avian species in Asian, European, and North American countries (Bui et al, 2012;Donis et al, 1989;Kang et al, 2013;Liang et al, 2015;Teng et al, 2012;Wu et al, 2015;Yuan et al, 2015). In recent years, multiple genotypes of H4 viruses have been shown to be co-circulating in the live poultry markets of Central, Eastern, and Southern China, and complex reassortment events between H4 subtype viruses and other subtype viruses (e.g., H3 subtype virus) have actively occurred in domestic ducks (Deng et al, 2013;Liang et al, 2015;Shi et al, 2016;Wu et al, 2015;Yuan et al, 2015). H4 subtype viruses can replicate in mice without prior adaptation and transmit between guinea pigs via direct contact (Kang et al, 2013;Liang et al, 2015).…”
Section: Accession Numbersmentioning
confidence: 99%
“…To further characterize the two viruses, eight fragments of each virus were amplified and sequenced as described previously (Shi et al., ). The sequences were deposited to GenBank with accession number of –.…”
mentioning
confidence: 99%
“…Additionally, mutations related to the enhanced virulence and transmission of influenza viruses in mammals, including PB2-627K and -701N, were also not observed in any of the four isolated viruses. H4N6 strains previously isolated from domestic ducks in China also did not possess these mutations related to mammalian adaptation [ 13 , 14 , 28 ]. Hossain et al demonstrated that duck influenza virus could acquire mammalian-associated genetic changes after adaptation in land-based birds, including chickens and quail [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been noted that H4N6 viruses have been repeatedly found in mammalian species, such as humans and pigs [ 7 11 ]. H4N6 is frequently isolated from domestic ducks in China [ 12 14 ]. Genetic analysis indicates that these H4N6 viruses are undergoing complex and frequent reassortment events.…”
Section: Introductionmentioning
confidence: 99%